Tun Dr. Mahathir’s vision 2020 universities:Views from the humanities. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2006)
Vision 2020, the most influential policy statement in Malaysia since independence, has generated intense national discussions and attracted widespread public support as well as criticisms.